2002
DOI: 10.1097/00000539-200202000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for Patients with Congenital Insensitivity to Pain and Anhidrosis: A Questionnaire Study in Japan

Abstract: We investigated the anesthetic management of patients with congenital insensitivity to pain and anhidrosis. We clarified the following three important points: anesthesia is necessary, temperature management must be maintained, and there must be sufficient perioperative sedation in the anesthetic management of patients with congenital insensitivity to pain and anhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
30
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 9 publications
1
30
0
2
Order By: Relevance
“…While Tamioka et al reported that all anesthetic agents could be safely used in these cases 12 , in another study which analyzed the anesthetic agents used in 358 procedures applied under general anesthesia to 35 CIPA syndrome patients, it was seen that thiopental was used in 4% of cases, ketamine in 27% and propofol in 71%, and in contrast, opioids were used in 8% and muscle relaxants in 27% 13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Tamioka et al reported that all anesthetic agents could be safely used in these cases 12 , in another study which analyzed the anesthetic agents used in 358 procedures applied under general anesthesia to 35 CIPA syndrome patients, it was seen that thiopental was used in 4% of cases, ketamine in 27% and propofol in 71%, and in contrast, opioids were used in 8% and muscle relaxants in 27% 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an absolute need for the administration of anesthesia during a surgical procedure and it has been reported that the type of anesthesia should be general anesthesia as the majority of these cases are mentally retarded pediatric cases 10,12 . In the case reported here, it was thought that ketamine and inhalation anesthesia would be sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that stress and anxiety may elevate body temperature and thus applying appropriate premedication is recommended. 4 Even though there may be a relationship between the development of hyperthermia and the use of anticholinergic drugs in patients with CIPA in the literature, there are case reports showing safe usage of these agents without inducing hyperthermia. 5 In our patient 0.2 mg of atropine was used safely during the perioperative period without inducing hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, patients with CIPA do not require analgesics for the maintenance of anesthesia, and are prone to become hemodynamically unstable with high concentrations of either volatile or intravenous anesthetics. Small doses of sedatives could achieve appropriate anesthetic depth in those patients [6,7]. The anesthetic regimen without opioids could diminish the risk of respiratory depression.…”
Section: Discussionmentioning
confidence: 99%